Genetic evaluation using next-generation sequencing of children with short stature: a single tertiary-center experience - Su Jin Kim; Eunyoung Joo; Jisun Park; Chang Ahn Seol; Ji-Eun Lee (Korean Society of Pediatric Endocrinology, 2024)
Purpose We used next-generation sequencing (NGS) to investigate the genetic causes of suspected genetic short stature in 37 patients, and we describe their phenotypes and various genetic spectra. Methods We reviewed the medical records of 50 patients who underwent genetic testing using NGS for suspected genetic short stature from June 2019 to December 2022. Patients with short stature caused by nongenetic factors or common chromosomal abnormalities were excluded. Thirty-seven patients from 35 families were enrolled in this study. We administered one of three genetic tests (2 targeted panel tests or whole exome sequencing) to patients according to their phenotypes. Results Clinical and molecular diagnoses were confirmed in 15 of the 37 patients, for an overall diagnostic yield of 40.5%. Fifteen pathogenic/likely pathogenic variants were identified in 13 genes (ACAN, ANKRD11, ARID1B, CEP152, COL10A1, COL1A2, EXT1, FGFR3, NIPBL, NRAS, PTPN11, SHOX, SLC16A2). The diagnostic rate was highest in patients who were small for their gestational age (7 of 11, 63.6%). Conclusions Genetic evaluation using NGS can be helpful in patients with suspected genetic short stature who have clinical and genetic heterogeneity. Further studies are needed to develop patient selection algorithms and panels containing growth-related genes.